(untitled) (Research, Society and Development, 2024)
This article explores the multiple impacts of online pornography consumption on adolescents, dividing the analysis into three main areas of impact: cerebral, psychological, and behavioral/social. Based on a narrative bibliographic review of publications from the last five years, following the methodology of Green, Johnson, and Adams (2006), the integrative and qualitative analysis encompassed recent studies on the topic. Frequent exposure to pornography is associated with anxiety, depression, low self-esteem, and risky sexual behaviors. Pornography activates the brain’s reward pathway, leading to desensitization and potential dependence. Socially, it perpetuates problematic gender norms and hinders the development of intimacy skills. The final considerations highlight the need for educational strategies and public policies that promote healthy sexuality and positive interpersonal relationships. It is essential that educators, parents, and health professionals address these issues in an informed manner, ensuring a safe environment for adolescent development.